Precast flat plate frame of buildings for renewal of the housing stock of Ukraine (Academic journal Industrial Machine Building Civil Engineering, 2024)
The suggested precast flat slab system is composed of columns and flat plates that connect to the columns without the use of consoles or capitals. This structural system is intentionally designed in such a way that lines of arrangement of plastic hinges between precast plates are artificially created. Consequently, an analysis of precast flat plate floor systems is proposed based on the yield line method. The utilization of the yield line method facilitates the development of straightforward engineering design schemes, potential fracture scenarios, and the determination of the load at which destructive failure occurs for all types of precast flat plates. By employing the yield line method within the ultimate equilibrium state, utilizing a nonlinear deformation model with an extreme criterion, design equations to address the bearing capacity of flat plate of the frame structural system are derived. These formulas are well-suited for practical engineering use and account for the plate's installation conditions as part of a precast flat floor.
Keywords: bearing capacity; building frame; flat plate; reinforced concrete; slab